A teoria das situações didáticas e o jogo da onça como opção estratégica de ensino - Alves, Elenice Carvalho (2023)
This work presents a contextualized approach to Combinatorial Analysis, aiming to develop logical mathematical reasoning, creativity, criticality and mathematical intuition, essential skills for the formation of students. Therefore, we resort to the use of playful activities in the classroom and problem solving. We use the Jogo da Onça, of indigenous origin, unknown to many, but with historical, cultural and mathematical richness. The game rules, the board and the pieces served as an inspiration in the elaboration of a list with 67 problems, which aim to analyze the ways of moving and capturing the pieces solving questions of combinatorial analysis and mathematical logic. The elaborated problems are part of a didactic situation, developed from Guy Brousseau’s theory and carried out in a public school. Thus, we conclude that it is possible to discuss and study issues related to indigenous culture in the classroom, complying with Law number 11.645/2008, and to teach mathematics from the resolution of interesting, challenging and significant problems.